Off You Go: Offerings in The Wailing, The Medium, and Mangkujiwo - Jannah, Rahmadina Vita; Nafi'ah, Fara Zhafira; -, Septiana; Millati, Cinta Fakhris; Kamila, Salsabila Rahma (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2025)
This study examined the differences in ritual offerings depicted in three different horror films: The Wailing (South Korea), The Medium (Thailand), and Mangkujiwo (Indonesia). The offerings used in these films demonstrated cultural ritual practices for interacting with spiritual entities. The aim of this research was to study the meaning and differences of the offerings displayed in the three films, where each element of the offering had its own significance within a particular culture. The ethnographic method of Spradley was used to collect research data through textual and visual analysis. The research findings, based on Raymond Firth's theory, categorized the offerings into three types: Personal, Value, and Voluntary. In Mangkujiwo, the offerings reflected the mysterious Javanese tradition, which involved communication with ancestors to seek their blessings. In The Medium, Thai shamans used offerings to maintain the balance between the supernatural and human realms. In contrast, in The Wailing, offerings were used in Korean culture to protect oneself from evil spirits. The differences in the traditions of offerings showed that, although the elements used were similar, offerings were more than just spiritual symbols; they also reflected profound cultural identities and values. Overall, this study revealed how Asian cultures understood and practiced their relationship with the spiritual world through offerings, aimed at fulfilling desires and seeking protection.